2019
DOI: 10.1093/biosci/biz131
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Risk Framework: Integrating Ecological Risk of Introduced Species with Recipient Ecosystems

Abstract: Global changes are predicted to facilitate the introduction, establishment, and spread of species into new environments leading to potential negative impacts on local biodiversity. Evaluating the risk associated with introduced species with a high likelihood of arrival, or species that have already been introduced, is therefore increasingly important. In the present article, we outline an operational framework to provide a basis for assessing the ecological risk of introduced species in order to facilitate jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…These evolutionary considerations may be useful additions to the list of criteria for assessing the vulnerability of native species and ecosystems to biological invasions, on which to base the assignment of priorities for surveillance and protection interventions [ 66 ]. These assessments tend to be based on ecological features (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These evolutionary considerations may be useful additions to the list of criteria for assessing the vulnerability of native species and ecosystems to biological invasions, on which to base the assignment of priorities for surveillance and protection interventions [ 66 ]. These assessments tend to be based on ecological features (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have used species distribution modeling (SDM) to predict the distribution of insect pests at local and global scales, while assessing the ecological risk of insect pests under climate change. [17][18][19]21,31,32 These studies showed that climate change may expand the distribution ranges of insect pests due to increasing species distribution probability. However, the application of SDM for assessing the ecological risk of insect pests may be limited, since the presence of one insect pest species is not directly linked to loss of natural resources, hindered societal development, or food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Global change, such as climatic warming, nitrogen deposition, and extreme hydrological events, could optimize the ecological and physiological traits of alien species, greatly facilitating their introduction and establishment in new habitats ( Wu and Ding, 2019 ; Probert et al., 2020 ). As an emerging driver of global change, plant invasions alter species interactions and threaten plant diversity and ecosystem functioning worldwide, causing serious damage to the associated microhabitats ( Ding et al., 2008 ; Sardans et al., 2017 ; Bernard-Verdier and Hulme, 2019 ).…”
Section: Introductionmentioning
confidence: 99%